MEDIA PAPAN BANGUN RUANG BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP DAN KEAKTIVAN SISWA KELAS II SD NEGERI - Setyarini, Jihan; Danuri, Danuri (Jurnal Riset Pendidikan Dasar (JRPD), 2025)
This research aims to 1) determine the effectiveness of the application of ethnomathematics-based space board making media on the ability to understand concepts for 2ð‘›ð‘‘ A and 2ð‘›ð‘‘ C grade students, 2) determine the effectiveness of the application of ethnomathematics-based space board making media on the activeness of 2ð‘›ð‘‘ A and 2ð‘›ð‘‘ C grade students, and 3 ) ethnomathematics-based space building board media is more effective than social-based image learning media on the ability to understand concepts and activeness of 2ð‘›ð‘‘ grade.This research was conducted at SD Negeri Jarakan in the 2024/2025 academic year, with subjects in 2ð‘›ð‘‘ A and 2ð‘›ð‘‘ C grade. This research was conducted using an experimental method using a Nonequivalent Control Group Design research design. Data collection techniques use tests and questionnaires. The data analysis techniques in this research are the instrument test class validity test, normality test, homogeneity test, and t test. Based on the research results, it was obtained 1) Normality and homogeneity it can be concluded that the ethnomathematics- based building board learning media is effective in increasing students' understanding of concepts in 2ð‘›ð‘‘ A and 2ð‘›ð‘‘ C grade. 2) Normality and homogeneity it can be concluded that the building board learning media based on ethnomathematics is effective in increasing the activity of students in 2ð‘›ð‘‘ A and 2ð‘›ð‘‘ C grade. 3) The research results are proven by the experimental class it can be concluded that ethnomathematics-based building board media is more effective than social- based picture learning media on the ability to understand concepts and activeness of 2ð‘›ð‘‘ grade.